Returning to Comfort Zones and Interdisciplinary Projects? One High School´s Experience in Southern Argentina - Carranza, Pablo Fabián (2019)
This article analyzes the capacity of teachers, administrators and students to move from areas that they consider to be outside of their comfort zone to areas where they feel relatively more comfortable or stable while participating in an interdisciplinary high school project executed in Patagonia, Argentina. The project was underway and halfway through completion when the protagonists, for different reasons, stopped to question continuing the project or not. Theoretical considerations for this study are based on the need for interdisciplinary integration that also include aspects of knowledge, time, community and people. It looks at different areas of everyday school life where these types of projects may be sustainable, particularly with regards to teaching and assessment criteria. For this case, the protagonists were ultimately faced with a need to reconstruct epistemological references.